Electrochemical preparation and characterisation of zinc oxide and poly(3,4-ethylenedioxythiophene)/zinc oxide thin films - Ismail, Abdul Hadi (2016)
The physical, chemical and electrochemical properties of zinc oxide (ZnO) and poly(3,4- ethylenedioxythiophene)/zinc oxide (PEDOT/ZnO) film electrode that were prepared electrochemically were studied. ZnO was electrodeposited on ITO glass substrate by applying five different electrodeposition potentials (-1.0 V, -1.3 V, -1.5 V, -1.7 V and -2.0 V), three different concentrations of the precursor solution (70 mM, 80 mM and 90 mM) and bath temperature (70 °C, 80 °C and 90 °C). The specific capacitance of the ZnO samples were observed to increase when the applied electrodeposition potential is increased from -1.3 V to -1.5 V. However, the specific capacitance is found to decrease when the applied electrodeposition potential is further increased to -1.7 V. PEDOT was potentiostatically deposited on the optimised hexagonal flake-like ZnO-covered ITO glass substrate by applying three different potentials (1.0 V, 1.25 V and 1.5 V) where under these circumstances, the effect of varying electropolymerisation potentials were studied. The optical band gap of each of the PEDOT/ZnO composites prepared were noticed to be within the range of 3.40 eV to 3.45 eV which were in between the optical band gap values of sole PEDOT and ZnO. The presence of both materials was asserted from XRD, FTIR and Raman spectroscopy analysis where all of the corresponding peaks for each of the materials in the spectra were assigned. SEM revealed the flake-like hexagonal morphology of ZnO which is in agreement with the XRD analysis. While the PEDOT morphology was discerned with round-shaped granular morphology where the average grain size decreased with the electropolymerisation potentials. The resistance of charge transfer of PEDOT/ZnO thin film is directly proportional to the electropolymerisation potential while on the specific capacitance was inversely proportional. The composite exhibit both PEDOT and ZnO unique properties that can be used as a multi-functional material in various potential applications.